2011
DOI: 10.3748/wjg.v17.i12.1622
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess: An audit of 10 years’ experience

Abstract: PLA is a diagnostic challenge, because the presentation of this condition is non-specific. Intravenous antibiotics and radiological drainage in the first instance allows resolution of most PLAs; However, a small proportion of patients still require surgical drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
102
3
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 18 publications
12
102
3
13
Order By: Relevance
“…7-9 However, Pang et al and Heneghan et al reported it to be 2:1 and 1.22:1, respectively. [10][11][12] In present study, alcohol was found to be a major risk factor as 48% cases were alcoholic. Ghosh et al had 72% alcoholic patients in their study.…”
Section: Discussionsupporting
confidence: 47%
“…7-9 However, Pang et al and Heneghan et al reported it to be 2:1 and 1.22:1, respectively. [10][11][12] In present study, alcohol was found to be a major risk factor as 48% cases were alcoholic. Ghosh et al had 72% alcoholic patients in their study.…”
Section: Discussionsupporting
confidence: 47%
“…12,13 In present study alcohol consumption was seen as a major risk factor as 58.4% patients of ALA were exposed to it, however only 14.2% of PLA cases were found alcoholic. It is contrary to the study of Islam QT et al which showed that indigenous alcohol has association with the development of pyogenic liver abscess.…”
mentioning
confidence: 47%
“…However, studies from west where PLA are more common, average age is above 60years. [12][13][14] As far as sex predisposition was concerned, after recruiting 50 consecutive patients, only 9 patients were female. Indian data show predominant male involvement; Sharma et al, Mukhopadhyay et al and Ghosh et al, reported male to female ratio to be 14.4:1, 7:1 and 11:1, respectively.…”
mentioning
confidence: 99%
“…Computed tomography (CT) abdomen showed multiple hypodense lesions in the The causative organism cannot be isolated in 21% of patients. 9 Pus, blood and pleural fluid cultures did not reveal any organism in our patient. Abscesses due to biliary sepsis, presence of shock, multiple abscesses are independent predictors of mortality.…”
Section: Discussionmentioning
confidence: 49%
“…Imaging guided needle aspiration was favoured over catheter drainage at our institution .Some groups prefer needle aspiration over catheter drainage, and some prefer catheter drainage over needle aspiration. 9 Multiple liver abscess have been rarely reported in world literature. Bahloul et al have reported a fatal case of multiple liver abscess in a 38 yr old woman which required surgical drainage.…”
Section: Discussionmentioning
confidence: 99%